Evaluation of antibacterial properties of Matricaria aurea on clinical isolates of periodontitis patients with special reference to red complex bacteria - Irfan Ahmad; Shadma Wahab; Nazima Nisar; Ayed A. Dera; Mohammad Y Alshahrani; Shahabe Saquib Abullias; Safia Irfan; Mohammad Mahtab Alam; Saurabh Srivastava (Elsevier, 2020)
Background: Chronic periodontitis has an interplay between different species of bacteria found in dental biofilms act a crucial role in pathogenesis and disease progression. The existing antibacterial therapy is inadequate, associated with many side effects as well as evolving multidrug resistance. Hence, novel drugs development with minimum or no toxicity is an immediate priority. Methods: Antibacterial efficacy of ethanolic extract of Matricaria aurea was tested against clinical isolates, ie. Treponema denticol, Tannerella forsythia, Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis from the patients with chronic periodontitis. Zone of inhibition, the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) were investigated by well diffusion method and micro broth dilution assay using alamar blue. Anti-virulence properties of the extract, which include adherence property and the biofilm formation, were investigated by adherence as well as biofilm formation assay. Results: Matricaria aurea extract showed potent inhibitory effect against pathogenic periodontal bacteria with the significant inhibitory zone (13-23 mm), MIC (0.39-1.56 mg/ml) as well as MBC (1.56-6.25 mg/ml). The M. aurea extract was able to inhibit bacterial adhesion ranged from 30 to 45%, 35 to 63% and 55 to 80% of MIC at MIC × 0.5, MIC × 1 and MIC × 2 respectively. Significant inhibition was found in biofilm formation to all the tested periodontal bacterial strains after the treatment with various concentrations of M. aurea extract for 24 and 48hrs. Conclusion: These results reveal for the first time that the Matricaria aurea extract might be the source of various compounds to be applied for chronic periodontitis therapy, which might draw these valuable compounds to the subsequent phase of development of the drug.